Efficacy of Blended E-Learning Tools: A Case Study - Jerold R. Thomas; Gregory A. Davis; Myra L. Moss (Journal of Applied Communications, 2008)
In the past 5 years, interest in distance learning has increased, and use of e-learning tools has become more widely accepted by academics. With such a wide variety of e-learning tools to choose from, what really works? How might we augment our traditional teaching tools with a blend of the new e-learning tools to better reach audiences? In this article, we discuss the efficacy of a set of blended e-learning tools — blogs, podcasts, enhanced podcasts, Internet telephony and instant messaging, news aggregators, collaborative project management software, and Web/video conferencing — used to teach Ohio State University (OSU) professionals about knowledge economy programming. We share implications of survey findings from this population and provide recommendations for others interested in initiating or improving their distance learning efforts with these tools.
Keywords: Efficasy; E-Learning; tools; Web/video conferencing; professionals; knowledge; blogs; podcasts